Social unrest in China: a bird's-eye view - Christian Göbel (Edward Elgar Publishing, 2019)
Featuring contributions from top scholars and emerging stars in the field, the Handbook of Protest and Resistance in China captures the complexity of protest and dissent in contemporary China, while simultaneously exploring a number of unifying themes. Examining how, when, and why individuals and groups have engaged in contentious acts, and how the targets of their complaints have responded, the volume sheds light on the stability of China's existing political system, and its likely future trajectory.